One hundred years of infection with three global pathogens in frog populations of Florida, USA. (May 2021) - Karwacki, Emily E.; Martin, Katherine R.; Savage, Anna E.
Abstract: Batrachochytrium dendrobatidis ( Bd ), Perkinsea ( Pr ), and Ranavirus ( Rv ) are three leading pathogens linked to amphibian declines, but much remains unknown about their origins and spread. Museum specimens are a critical resource for resolving epidemiological patterns because they can elucidate infection dynamics and their relationship with disease outbreaks. Here, we established a timeline of Bd, Pr, and Rv presence in anurans in Florida, USA, a region of high amphibian diversity. We measured pathogen prevalence and pathogen intensity in museum specimens of the genus Rana, a widely infected host lineage. We also sequenced barcoding regions to determine whether genetic lineages varied over time. Before this study, the first documented cases of Bd, Pr, and Rv in Florida were in 2009, 2002, and 2002, respectively. We detected all three pathogens nearly a century earlier, with the earliest Bd and Pr detections in 1928 and the earliest Rv detection in 1922. Prevalence and intensity varied across host species, geographic regions, life stages, and decades, with unique patterns for each pathogen. While we were unable to recover robust sequence data for Rv, the Bd and Pr sequence data showed no genetic variation over time. We found significantly more co-detection of Pr and Rv compared to any other pathogen combination, and to our knowledge, we also detected the first simultaneous tri-detection of Bd, Pr, and Rv . Overall, this study represents considerable extension of the timing and understanding of amphibian pathogens in the southeastern USA. Highlights: Bd, Pr, and Rv have been in Florida since at least 1928 and 1922 in regions not previously documented This study represents the first documented tri-infection with Bd, Pr, and Rv This study represents the first documented occurrence of Pr in three frog species